Planning for success : project management strategies for system integration projects at HP services Thailand - Muthian, Palanichamy; Johri, Lalit M.; Venkatesk, Sundar; Do, Ba Khang; Lacrosse, Ludovic (Pathum Thani, Thailand : Asian Institute of Technology, 2003)
In Thailand, HP Consulting and Integration (CI) business unit's major business focus is on System Integration (SI) engagements. System Integration Projects are generally complex undertakings, which use a wide range of resource over a period of time. These resources, and their interactions and time span must be properly managed. A critical success factor for a System Integrator like HP CI, is winning the "right" projects and the management of the project in the "right" way to success. In the recent past HP CI has seen many SI projects were discontinued and declared sick projects, some of them delayed and some of them got completed on time. This study aims to study such delayed/failed SI projects; analyze the major cause of project delays and failures and to recommend specific guidelines for the project team.
A research study submitted in partial fulfillment of the requirements for the degree of Master in Business Administration (Executive)
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2003
Keywords: Project management -- Thailand; Strategic planning -- Thailand